Legal Aspects of Personal Data Protection in the Implementation of Regional E-Government - Evangelista, Beverly; Daulay, R. Fahmi Natigor (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The transformation of government services from manual systems to digital platforms through e-government in Indonesia is a response to the advancement of information and communication technology (ICT) and the demand for bureaucratic efficiency. Presidential Instruction No. 3 of 2003 marked the initial milestone in e-government development, which has since evolved into various digital public services such as OSS, SatuSehat, and Satu Data Indonesia. This study employs a normative legal method using statutory, conceptual, and normative gap analysis approaches. The focus of the research is directed at two main aspects: the regulation of personal data protection within regional e-government systems and the normative weaknesses in ensuring the security and confidentiality of citizens’ data. The discussion reveals that despite the enactment of the Personal Data Protection Law (PDP Law), its implementation at the regional level faces significant challenges, including overlapping regulations, lack of technical standards, weak oversight, and ineffective sanctions. Regional governments often lack clear operational guidelines, resulting in disparities in data protection across regions. The study concludes that personal data protection must be an integral part of digital governance system design. Regulatory reform, institutional capacity building at the regional level, and the establishment of effective oversight mechanisms are strategic steps to ensure comprehensive protection of citizens’ privacy rights in the digital era.